2018
DOI: 10.1186/s13054-018-2123-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperoxia on vascular tone in animal models: systematic review and meta-analysis

Abstract: BackgroundArterial hyperoxia may induce vasoconstriction and reduce cardiac output, which is particularly undesirable in patients who already have compromised perfusion of vital organs. Due to the inaccessibility of vital organs in humans, vasoconstrictive effects of hyperoxia have primarily been studied in animal models. However, the results of these studies vary substantially. Here, we investigate the variation in magnitude of the hyperoxia effect among studies and explore possible sources of heterogeneity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 88 publications
0
9
0
1
Order By: Relevance
“…It is currently inferred that oxidative stress can cause vasoconstrictive effects [ 21 ]. Smit et al [ 22 ] systematically reviewed 60 experimental animal studies and found that excessively high PO 2 can cause vasoconstriction in vivo and in vitro, and there was a clear dose dependent effect. Smit et al [ 23 ] also systematically reviewed 33 clinical studies and found that excessively high PO 2 (234–617 mmHg) can increase vascular resistance by 11–16% in healthy people and 24.6% in patients with heart failure, and can decrease cardiac output by 10.2% in healthy people, 9.6% in patients with coronary heart disease, and 15.2% in patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently inferred that oxidative stress can cause vasoconstrictive effects [ 21 ]. Smit et al [ 22 ] systematically reviewed 60 experimental animal studies and found that excessively high PO 2 can cause vasoconstriction in vivo and in vitro, and there was a clear dose dependent effect. Smit et al [ 23 ] also systematically reviewed 33 clinical studies and found that excessively high PO 2 (234–617 mmHg) can increase vascular resistance by 11–16% in healthy people and 24.6% in patients with heart failure, and can decrease cardiac output by 10.2% in healthy people, 9.6% in patients with coronary heart disease, and 15.2% in patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperoxia is one of a well-identified PCh inhibitors; however, it also exerts direct vasoconstrictive effect 12 14 . In healthy and HFrEF subjects prolonged hyperoxic exposure increases systemic vascular resistance (SVR) 13 , 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…49,78 A meta-analysis looking at all in vivo and ex vivo animal studies of oxygen-induced vasoconstriction concluded that vasoconstriction was directly proportional to the degree of oxygen exposure, and greatest within the vascular smooth muscle. 79 High FiO 2 may also contribute to peripheral and coronary vasoconstriction during anaesthesia, increasing tissue ischaemia.…”
Section: Discussionmentioning
confidence: 99%